MOTIVATION AND LEARNING STYLE: DO THEY CORRELATE WITH LANGUAGE PROFICIENCY? - Udin Kamiludin (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2019)
This paper discusses the issues of motivational orientation, learner types and their relationship with English Language Proficiency among the students of semester one in the academic year 2018 / 2019 at the State Institute of Islamic Studies Syekh Nurjati, Cirebon. It is a survey research. The data were obtained through the questionnaires i.e. the Attitude / Motivation Test Battery (AMTB) developed by R.C Gardner, and â€œHow do you learn best?â€ adapted from K. Willingâ€™s model. And the Standardized Test of English was designed adopting the TOEFL model. The statistical software such as SPSS was employed to analyze the data.The results show most of the participants are instrumentally motivated learner and are communicative as well as teacher-oriented types, and majority of them are of medium level of English Language Proficiency.Furthermore, the findings reveal that an integrative motivated learners scored better than Â instrumentally motivated learners in English Language Proficiency Test. This means motivation correlates with English Language Proficiency. Whereas, learning style does not correlate with English Language Proficiency. However, the result of correlation test confirms the r score (0.456) is more than t table score (0.2441); which means the H0 hypothesis is rejected. Thus, Motivation and Learning Style correlate with English Language Proficiency. The findings led to conduct further research on motivating students as to improve their level of English language proficiency.